Concentration and composition of bioaerosol emissions from intensive farms: pig and poultry livestock - Gladding, Toni Lesley; Rolph, Catherine A.; Gwyther, Ceri L.; Kinnersley, Robert P.; Walsh, Kerry A.; Tyrrel, Sean F. (Elsevier, 2020)
Intensive farming is widespread throughout the UK and yet the health effects of bioaerosols which may be generated by these sites are currently not well researched. A scoping study was established to measure bioaerosols emitted from intensive pig (n = 3) and poultry farms (n = 3) during the period 2014–2015. The concentration of culturable mesophilic bacteria, Gram-negative bacteria, Staphylococcus spp., and fungi selecting for presumptive Aspergillus fumigatus were measured using single-stage impaction Andersen samplers, whilst endotoxin and (1 → 3)-β-D-glucan was undertaken using inhalable personal samplers. Particulate matter concentration was determined using an optical particulate monitor. Results showed that culturable bacteria, fungi, presumptive Staphylococcus aureus (confirmed only as Staphylococcus spp.) and endotoxin concentrations were elevated above background concentrations for distances of up to 250 m downwind of the source. Of all the culturable bioaerosols measured, bacteria and Staphylococcus spp. were identified as the most significant, exceeding published or proposed bioaerosol guidelines in the UK. In particular, culturable Staphylococcus spp. downwind was at least 61 times higher than background at the boundary and at least 8 times higher 70m downwind on the four farms tested. This research represents a novel dataset of intensive farm emissions within the UK. Future research should exploit the use of innovative culture-independent methods such as next generation sequencing to develop deeper insights into the make-up of microbial communities emitted from intensive farming facilities and which would better inform species of interest from a public health perspective
Keywords: Air sampling; Endotoxin; Agriculture; Intensive farming; Bioaerosols